Development of a Q‐Sort Version of the Defense Mechanism Rating Scales (DMRS‐Q) for Clinical Use. Issue 5 (4th April 2014) - Di Giuseppe, Mariagrazia; Perry, J. Christopher; Petraglia, Jonathan; Janzen, Jennifer; Lingiardi, Vittorio
<x xml:space="preserve">Abstract</x> This report focuses on the need to provide clinicians with a reliable and valid measure for detecting patient defense mechanisms "inside psychotherapy." To avoid the limitations of existing methods, we designed a Q‐sort based on the theoretical definitions and criteria of the Defense Mechanisms Rating Scales (DMRS‐Q), but one that does not require transcripts of clinical interviews or sessions and may be applied without specific training on defenses. The DMRS‐Q is sensitive to changes in psychotherapy and its scores correlate significantly with various aspects of mental functioning, making it potentially available for the psychotherapy process and outcome research as well. We report the results of using the DMRS‐Q on a systematic single case study with the aim of detecting changes in defense mechanisms during a long‐term psychodynamic psychotherapy. The DMRS‐Q reveals change both in quantitative scores and in the literary Defensive Profile Narrative.